EVALUASI KELAYAKAN KREDIT DENGAN METODE CLASSIFICATION AND REGRESION TREE (CART) - Mirfan Mirfan (Lembaga Penelitian dan Publikasi Nobel Indonesia, 2013)
Credit worthiness evaluation is an important element in the provision of credit to borrowers. Lending activities required a good and thorough analysis of all aspects of credit that supports the credit granting process, in order to prevent the occurrence of a credit risk. The purpose of this study was to determine the creditworthiness of the debtor by Classification Methods and Regresion Tree (CART). One of the results of assessment of the Credit Application form to obtain credit worthiness statement that can be classified under several conditions, namely: viable with very low risk, decent high-risk, less worthy, and very less feasible.